(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
A new control scheme to improve and maintain the power quality of an electrical power system by design of distributed power flow controller. Generally, In case of modern power utilities have problems like challenges in growth of electricity in case of non-linear loads in grid connected systems. In this paper, we introduced a new FACTS method i.e. distributed power flow controller which is similar to other series-shunt controller types. This DPFC method is also used like UPFC to mitigate voltage sag and swell as a power quality issue. In DPFC, we eliminate the common dc link capacitor and instead of single three phase series converter it has three individual single phase converters. In this paper the control circuit is designed by using series referral voltages, branch currents. The evaluated values are obtained by using MATLAB/SIMULINK.